Early diagnosis of symptoms and effective therapy of hypoglycemia in piglets (Mongolian Journal of Agricultural Sciences, 2024)
The aim of the study was to study the main etiological factors of hypoglycemia in newborn piglets, to establish criteria for a comprehensive diagnosis of the disease, as well as to develop an optimal treatment regimen. The materials obtained in the course of the study are of great importance for the clinical assessment of piglets' health. On the other hand, it expands knowledge in understanding this pathology and allows for effective therapeutic and preventive work in industrial pig breeding complexes.In the studied group of animals, a significant decrease in blood glucose was recorded to 3.49±0.03 mmol/l on the second day of life and to 2.75±0.03 on the 4th day, when the piglets were in a coma. The indicators of erythrocytes, hemoglobin and iron, which were also reduced by 35%, 57.9% and 57.1%, respectively, indicate that the young have signs of alimentary anemia. As a therapeutic technique, it is effective to use a 15% glucose solution and plant piglets under healthy sows. Due to this, on the 10th day, the blood glucose level of piglets rose to 5.25± 0.04 mmol/l. Of the 90 sick piglets on the farm, 78 recovered, the percentage of young animals was 84.6%. The greatest effect is observed with the intraperitoneal method of administration of a 15% solution in a dose of 5-10 ml, which increases the percentage of recovery to 92%. For the highest results, it is recommended to use ferran preparations in a dose of 2 ml and nitamine 0.4 ml per 10 kg of weight as additional therapy, as well as warming piglets with infrared lamps.